Comparison of visual assessment and heart girth tape measurement for estimating the weight of cattle in clinical practice. Issue 3 (March 2015) - Wood, Sarah; Reyher, Kristen K.; Barrett, David C.
Highlights Visual weight estimation was compared with an indirect measure of body weight in Holstein cattle. Visual weight estimation was variable in accuracy. Overestimation tended to occur at higher body weights. Underestimation tended to occur at weights less than 150 kg. Inaccuracy is sufficient to affect management and treatment decisions.